2017
DOI: 10.1016/j.neuron.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Medial Prefrontal Cortex Reduces Memory Interference by Modifying Hippocampal Encoding

Abstract: Summary The prefrontal cortex (PFC) is crucial for accurate memory performance when prior knowledge interferes with new learning, but the mechanisms that minimize proactive interference are unknown. To investigate these, we assessed the influence of medial PFC (mPFC) activity on spatial learning and hippocampal coding in a plus maze task that requires both structures. mPFC inactivation did not impair spatial learning or retrieval per se, but impaired the ability to follow changing spatial rules. mPFC and CA1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
171
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(197 citation statements)
references
References 50 publications
12
171
2
Order By: Relevance
“…A wealth of research suggests that prefrontal-hippocampal interactions mediate cognitive control processes that select representations for encoding or retrieval from memory (see e.g., Eichenbaum, 2017;Simons & Spiers, 2003, for reviews). These control processes might promote interference resolution by modifying hippocampal representations (Benoit, Hulbert, Huddleston, & Anderson, 2015;Guise & Shapiro, 2017;Rajasethupathy et al, 2015;Shimamura, Jurica, Mangels, Gershberg, & Knight, 1995). Supporting this possibility, we saw prior knowledge lead to greater hippocampal-prefrontal interactions during learning and greater subsequent separation in hippocampal representations thereafter.…”
Section: Shifting the Direction Of Hippocampal Learningsupporting
confidence: 57%
“…A wealth of research suggests that prefrontal-hippocampal interactions mediate cognitive control processes that select representations for encoding or retrieval from memory (see e.g., Eichenbaum, 2017;Simons & Spiers, 2003, for reviews). These control processes might promote interference resolution by modifying hippocampal representations (Benoit, Hulbert, Huddleston, & Anderson, 2015;Guise & Shapiro, 2017;Rajasethupathy et al, 2015;Shimamura, Jurica, Mangels, Gershberg, & Knight, 1995). Supporting this possibility, we saw prior knowledge lead to greater hippocampal-prefrontal interactions during learning and greater subsequent separation in hippocampal representations thereafter.…”
Section: Shifting the Direction Of Hippocampal Learningsupporting
confidence: 57%
“…Since our results show that both theta and RR exist in these regions, such experiments warrant being revisited with simultaneous recordings of respiration. Finally, we also suggest that the "4-Hz oscillation" described to link mPFC, ventral tegmental area and hippocampus during working memory (Fujisawa & Buzsáki, 2011;Guise & Shapiro, 2017; see also Roy et al, 2017), and to coordinate mPFC and amygdala networks during fear learning Karalis et al, 2016), may correspond to respiration-coupled oscillations.…”
Section: Discussionmentioning
confidence: 64%
“…We found that during model-based inferences, RTs and neural activity in EC, vmPFC/mOFC, and lOFC reflected the Euclidian distance of navigational trajectories on 2-D space via relevant hubs, over and above the behaviorally-relevant 1-D ranks. Notably, cells encoding the distance to "goals" have been documented in EC and mPFC of rodents (Boccara, Nardin, Stella, O'Neill, & Csicsvari, 2019;Butler et al, 2019;Guise & Shapiro, 2017) when navigating in physical space, while the rodent OFC has been shown to be necessary for modelbased inferences (Jones et al, 2012). A separate body of work in humans and monkeys during value-based choice has consistently found value comparison signals thought to guide goal-based choices in vmPFC/mOFC FitzGerald et al, 2009;Hunt et al, 2012;Lim et al, 2011;Nicolle et al, 2012;Papageorgiou et al, 2017;Rushworth et al, 2011;Strait et al, 2014).…”
Section: Discussionmentioning
confidence: 99%